Educação musical e unidocência: modos de ser professora na educação infantil - Kolling, Luciane Inês (2023)
The present dissertation has as research theme, Music Education in practices of uniteacher reference teachers in Early Childhood Education revealed in their ways of being a teacher. As a general objective, we sought to understand how teachers of Early Childhood Education, preferably graduates of the Pedagogy course at the Federal University of Santa Maria, constitute their teaching ways with music in the school space. Specifically, we sought to identify why, in what way and at what moments singleteacher teachers work with music in the school space; to know which practices are most developed by single-teacher teachers to work with children in music; understand how single-teacher teachers interrelate musical learning experiences in the set of other fields of experience. As a source of data production for qualitative research (BRANDÃO, 2001; MINAYO, 2009) two research instruments were used: semi-open questionnaire (GIL, 1999; BABBIE, 2003) and focus group (BAUER; GASKEL, 2002; GATTI, 2005; OLIVEIRA, et al. 2020). For the analysis of the narratives, the comprehensive-interpretative analysis was used (SOUZA, 2006, 2014). The analyzes carried out are presented by five Thematic Analysis Units: “Working with music”, “The teacher's role”, “Musicalizing”, “A sensitive listener” and “Children's songs”. From the above, it is important to reflect on the professional who graduated from the Pedagogy course and their ways of being a single teacher, on being a reference teacher who enhances music in their classroom and deepens their repertoire of knowledge and knowledge about the world, for and with children in Early Childhood Education.